Pengaruh Kualitas Layanan Perbankan Terhadap Kepuasan dan Loyalitas Nasabah Bank Syariah XYZ di Jakarta - Hendri Wijaya; Irfan Syauqi Beik; Bagus Sartono (School of Business, Bogor Agricultural University (SB-IPB), 2017)
The competition of the banking industry requires Islamic bank to provide a great services to its customers. Service quality is one of the critical points for the banking industry. Good quality services will create customer satisfaction and encourage customer loyalty. The purpose of this research is to analyze the factors that affect customer satisfaction and loyalty of Islamic bank. This research uses the concept of Banking Service Quality (BSQ) which is consisting six dimensions: effectiveness and assurance, access, price, service portfolio, reliability, and tangible. BSQ concept is later developed into the Islamic Banking Service Quality by adding a dimension that is Sharia compliance. Thus forming seven dimensions in measuring customer satisfaction of Islamic banks. The research method using Structural Equation Modeling (SEM), respondents are customers of Bank Syariah xyz, sampling technique used is convenience sampling with 160 persons of sample size. The results showed that only four dimensions of price, service portfolio, reliabililty, and tangible has positive effect on customer satisfaction, and customer satisfaction has positive influence on customer loyalty. While the three other dimensions have no effect on customer satisfaction.Keywords: Islamic bank, service quality, SEM, customer satisfaction, customer loyaltyAbstrak: Persaingan yang ketat industri perbankan menuntut bank syariah harus mampu menyediakan layanan yang berkualitas bagi para nasabahnya. Kualitas layanan menjadi salah satu poin kritis bagi industri perbankan yang bergerak di sektor jasa. Kualitas layanan yang baik akan menciptakan kepuasan nasabah dan mendorong loyalitas nasabah. Tujuan dari penelitian ini adalah untuk menganalisis faktor-faktor yang memengaruhi kepuasan dan loyalitas nasabah bank syariah. Pengukuran kepuasan nasabah dalam penelitian ini menggunakan konsep Banking Service Quality (BSQ) yang terdiri dari enam dimensi yaitu effectiveness and assurance, access, price, service portfolio, reliability, dan tangible. Konsep BSQ kemudian dikembangkan menjadi Islamic Banking Service Quality dengan menambahkan satu dimensi, yaitu Sharia compliance. Sehingga terbentuklah tujuh dimensi dalam mengukur kepuasan nasabah bank syariah xyz. Metode penelitian menggunakan Structural Equation Modeling (SEM), responden adalah para nasabah bank syariah xyz, teknik pengambilan sample menggunakan convenience sampling dengan jumlah responden sebesar 160 orang. Hasil penelitian menunjukkan bahwa hanya dimensi price, service portfolio, reliabililty, dan tangible berpengaruh positif terhadap kepuasan nasabah dan kepuasan nasabah berpengaruh positif terhadap loyalitas nasabah. Sedangkan ketiga dimensi lainnya tidak berpengaruh terhadap kepuasan nasabah.Kata kunci: bank Syariah, kualitas layanan, SEM, kepuasan nasabah, loyalitas nasabah